Optimization of KY-crystallization process - Kryvonosov, Ie.V.; Lytvynov, L.A. (Functional Materials, 2017)
The Kyropoulos method is an efficient means for growth of large high-quality single crystals. Technologists try to use the methods of numeral simulation for analytical calculation of thermodynamic conditions of crystallization and the choice of optimal technological regimes. However, these methods do not permit to effectively use the calculation results for prediction of the crystal growth dynamics and correction of the crystallization regime. In the present work it is described a method for optimization of sapphire crystallization process, based on the analysis of dynamic characteristics of the virtual image of the real technological process.